Laju Pertumbuhan Harian dan Sintasan Ikan Ili (Homaloptera sp.) pada Proses Domestikasi dengan Pemberian Pakan yang Berbeda - Ariga, Fitri; Hasri, Iwan; Fahmi, Rizkan; Susanti, Zulida (MAHSEER: Jurnal Ilmu-Ilmu Perairan dan Perikanan, 2022)
This study aimed to analyze the daily growth rate and survival rate of Ili fish (Homaloptera sp.) fed different feeds. This study used a completely randomized design consisting of four treatments and three replications, namely Tubifex, earthworms, submerged commercial feed and floating commercial feed. The results showed that ili fish fed different feeds had a significant effect on daily growth rate and survival. The best daily growth rate values ​​were found in thetreatmentTubifex and floating commercial feed. The best survival value in the treatment of earthworms and floating commercial feed